Distribution modeling of Amblyomma rotundatum and Amblyomma dissimile in Brazil: estimates of environmental suitability - Polo, Gina; Luz, Hermes R.; Regolin, André Luis [UNESP]; Martins, Thiago F.; Winck, Gisele R.; da Silva, Hélio R.; Onofrio, Valeria C.; Labruna, Marcelo B.; Faccini, João L. H. (Springer Nature, 2021)
The number of reports of tick parasitism in amphibians and reptiles has increased over the past few years, including new host and location records for Amblyomma rotundatum and Amblyomma dissimile. However, knowledge of the geographical distribution remains incomplete, and in many regions of Brazil, the presence of these vectors has not been investigated. Several candidate models were built using a correlative maximum entropy approach, and best-fitting models were selected based on statistical significance, predictive ability, and complexity based on current climatic trends and future projected climate changes. Final models showed a good ability to discriminate A. rotundatum and A. dissimile current and future potential distributions. The entire country had higher predicted suitability for A. rotundatum while A. dissimile was mainly restricted to the Amazon and Pantanal biomes. A. rotundatum is a species with enormous potential for dissemination in the next decades, potentially through the legal and illegal transport of reptiles and amphibians. The proposed model is useful for targeting surveillance efforts increasing the efficiency and accuracy of future ecological research and tick management efforts.
Keywords: Amphibians; Climate change; Reptiles; Species distribution modeling; Ticks